DISSEMINATION SPECIFIC TECHNOLOGY RAINFED RICE THROUGH PTT APPROACH - Muhammad Thamrin; Desi Ardilla; Riswan Rudyanto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Dissemination is the activity of action-reaction not only affects the mindset of the target group but can also be the person who brings the innovation itself. The notion that the new dissemination carried out after the completion of the research process, in principle needs to be changed. Dissemination process has to take place during the research process begins proportionally. This study aims to identify the potential, constraints, and opportunities for the development of rainfed lowland rice through the approach of Integrated Crop Management, an innovative approach in order to increase the efficiency of paddy rice by combining various technology components, including specific technologies that support each other with regard to the use of resources wisely nature that impact the growth and productivity of plants. The method used is to assess the needs and opportunities of rainfed rice farmers in the WKPP Paya Itik Desa Nogorejo. Based on the research needs and opportunities then drafted the main technological packages which are then studied and practiced together between farmers, researchers and agricultural extension as a facilitator, to conduct a demonstration plot of 1 Ha. The results showed that the main obstacle to scale farmers first priority is the seed, and the productivity of rainfed rice integrated crop management approaches have increased an average of 1.1 tons / ha (tile), with the value of B / C ratio 1, 42.Keywords: Rice Rainfed , Integrated Crop Management , Productivit